Body Movement and Nonverbal Communication An Annotated Bibliography, 1971-1981 - Skupien, Janet; Davis, Martha (Indiana University Press, 1982)
Researchers and students of body movement and nonverbal communication will find this annotated bibliography an indispensable guide to the literature on the subject that has been produced over the last decade. The editors' objective was not so much to evaluate works as to give readers enough information to determine if a specific text is relevant to their interests. The bibliography includes works published in six languages that are directly concerned with the psychology or anthropology of body movement. Articles or books from areas such as dance therapy, motor learning, psycholinguistics, ethology, and physical education are included only if they deal in some way with behavioral aspects of movement per se and if they are focused clearly on body language-particularly research in body language as opposed to clinical or training program reports. The bibliography reveals that in the 1970s researchers applied more rigorous methods of assessment, sampling, manipulation, and statistical analysis to the study of nonverbal behavior. Body Movement and Nonverbal Communication will stimulate interest and further research in an area that has produced some exciting discoveries about human behavior.